Chiral Brønsted Acid‐Catalyzed Asymmetric Synthesis of N‐Aryl‐cis‐aziridine Carboxylate Esters. Issue 19 (5th April 2017) - Bew, Sean P.; Liddle, John; Hughes, David L.; Pesce, Paolo; Thurston, Sean M.
Abstract: We report a multi‐component asymmetric Brønsted acid‐catalyzed aza‐Darzens reaction which is not limited to specific aromatic or heterocyclic aldehydes. Incorporating alkyl diazoacetates and, important for high ee's, ortho‐tert‐butoxyaniline our optimized reaction (i.e. solvent, temperature and catalyst study) affords excellent yields (61–98 %) and mostly >90 % optically active cis‐aziridines. (+)‐Chloramphenicol was generated in 4 steps from commercial starting materials. A tentative mechanism is outlined. Abstract : Nice and easy : An efficient one‐pot synthesis of chiral non‐racemic aziridines was achieved by using 1 mol % of a readily available Brønsted acid catalyst. The introduction of an ortho ‐ tert ‐butoxy group on the N ‐aryl ring was critical to inducing high levels of optical activity in the products. By using this protocol a simple 4‐step synthesis of the antibiotic (+)‐chloramphenicol was realized.